A STEREOLOGICAL STUDY OF HIPPOCAMPUS IN EXPERIMENTAL EPILETIC RAT MODEL TREATED WITH ACORUS CALAMUS AND BETA-ASARONE - C, Venkataramaniah; Praba A, Mary Antony (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Epilepsy is the fourth most prevalent neurodegenerative disorder that affects about 1–2% of people round the world. Epilepsy cannot be cured even with modern medication, but the medications can control the seizures. Even this cannot be achieved in nearly 30% of epileptic population. At this point, we felt the need of some natural supplements to protect the nervous system against neurodegeneration and so created an equivalent model of epilepsy with kainic acid lesion and studied the novel role of Acorus calamus in protecting the neurons. Methods: For this study, we divided the animals into four groups, based on the drugs used. We also produced a stereotaxic model of epilepsy by inducing kainic acid into the right hippocampus of all the animals except CO (control) group. Then, we conducted a stereological study both on the 2nd and 7th day after surgery, to rule out the neuroprotective and neuroregenerative ability of the drugs employed. Results: The results were amazing. Stereological study on the 2nd day revealed a very large lesion on the hippocampus of lesion control (LC) animals, and the lesion was very much smaller in both drug group animals. On the 7th day also the LC animals showed a large lesion, but the lesion on the drug group animals diminished due to a number of new cells, probably of neurons grown in the place of lesion. Conclusion: The results proved the neuroprotective and regenerative ability of both drugs, but as a fact, beta-asarone had an upper hand in this study.